Growth, disparities and inclusive development in india : Perspectives from the Indian state of Uttar Pradesh - Mamgain, Rajendra P. (Singapore : Springer Nature, 2019)
The book suggests strategies for promoting high and sustained economic growth, and highlights the significance of broadening social inclusiveness through greater and more rapid access to economic and social opportunities, and building strong social safety nets to protect the chronically poor and mitigate their risks and vulnerabilities with the help of good governance and institutions. With contributions from leading scholars from the region, it is a valuable resource for researchers working in the area of growth and inequality, as well as for policy makers from developing economies around the globe.
Keywords: Employment -- Uttar Pradesh, India; Socio-cultural change -- Uttar Pradesh, India; Economic growth -- Uttar Pradesh, India